(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
Bitter leaf possesses medicinal, pharmaceutical and bioprotective properties aside its nutritional importance. However, there is a dearth of documented information on the production requirements of this important crop as pot-plants with regards to fertilizer source and rates. A pot experiment was conducted at Crop Science and Horticulture Teaching and Research Farm, Nnamdi Azikiwe University, Awka to study the effect of organic fertilizer types (poultry manure, cow dung, poultry manure + cow dung) and rates (0, 5, 10, 15 t ha-1) on the growth, fresh leaf yield and dry matter partitioning of bitter leaf. The experiment was laid out as 3x4 factorial experiment fitted into completely randomized design (CRD) and replicated ten times. Data were collected on growth and fresh leaf yield. Organic fertilizer types and rates and the interaction significantly (P<0.05) influenced the growth and yield of bitter leaf. Applications of 10 t ha-1 poultry manure or combined application of poultry manure and cow dung at 10 t ha-1 significantly (P<0.05) produced tallest plants and highest number of leaves. The combined application of poultry manure and cow dung also produced highest fresh leaf yield (2.15 t ha-1). This was followed with poultry manure applied at either 10 or 15 t ha-1 (1.96 and 1.97 t ha-1, respectively). It was therefore recommended that growers should apply poultry manure at 10 t ha-1 or combination of poultry manure and cow dung at 10 t ha-1 for enhanced growth and leaf yield of bitter leaf in containers.